Liming of "Latossolo roxo álico fase cerrado" soil and its effect on forage sorghum plant development - Seiffert, Nelson F.; Soares, Wilson V.; Schunke, Roza M.; Primo, Armando T. (Pesquisa Agropecuaria Brasileira, 2014)
The present investigation was carried out in Campo Grande, MS, Brazil, to determine the influence of lime application on "Cerrado" Soil, and its effects in the growth of forage sorghum. Three experiments were established. The first, a comparison of twelve sorghum cultivars, was conducted under field conditions. Despite a NPK fertilization, the sorghum had poor development and dry matter (DM) production, and showed phosphorus deficiency symptoms. The other trials were done in greenhouse. The second one measured the effects of combinations of lime and other macro and micro nutrients on the growth of sorghum. Twenty-four treatments with three replications were compared. Only when phosphorus and lime were present was a normal development of the sorghum recorded. The last greenhouse trial studied three regional sources of lime at seven levels. Observations were made on the effect on the soil pH, Aluminum levels and DM production at 50 days after sowing. The comparisons showed that all three commercial sources of lime had similar effects in correcting the hydrolitic acidity and Aluminum toxicity (P <0,05). A reduction to a level near 0,4 me/100 g soil in Aluminum, which is not detrimental to plants, was obtained with an application of 2 t per hectar of lime. To obtain a pH of 6,0 to 6,5 in this soil, it was necessary to use 5 t per hectar of lime. The greatest dry matter accumulation of sorghum plants was reached with 6 t per hectar of commercial lime.